2013
DOI: 10.2147/mder.s50088
|View full text |Cite
|
Sign up to set email alerts
|

Validation and ease of use of a new pen device for self-administration of recombinant human growth hormone: results from a two-center usability study

Abstract: Close adherence to the recommended treatment regimen is important for the success of recombinant human growth hormone therapy, although nonadherence can be common. Ease of use and safety during use/storage are among several important factors in the design of a growth hormone injection device intended for long-term use. This study was performed to validate the usability and assess the ease of use of a new pen device (SurePal™) that has been developed to support daily administration of the recombinant human grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 30 publications
(22 reference statements)
0
17
0
Order By: Relevance
“…Devices that are easier to use can improve a patient’s ability and willingness to comply with treatment. It has been reported that the choice of an adequate drug delivery device is associated with greater patient compliance and improved clinical outcomes 12,13…”
Section: Discussionmentioning
confidence: 99%
“…Devices that are easier to use can improve a patient’s ability and willingness to comply with treatment. It has been reported that the choice of an adequate drug delivery device is associated with greater patient compliance and improved clinical outcomes 12,13…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of participants overall found SurePal™ very easy or easy to use for injection, which is a factor associated with choice of device and successful adherence with treatment. 7 , 11 SurePal™ has various features that may have contributed to patients rating of the device as easy to use. These include an autopriming feature, cartridges that are preassembled and ready to use, a sliding injection button that requires minimum force to perform an injection, and a dose-memory function that enables the correct dose to be preset and locked into the device.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Improving adherence to therapy may be challenging, given the need for long-term subcutaneous administration of rhGH. 7 Enhanced self-administration devices may play a role in improving adherence. 2 , 3 Device-related factors affecting adherence include the patient’s preference for the delivery device, its simplicity, convenience, and ease of use, together with the provision of appropriate education and training in the administration technique.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations